Analysis of the Effect of Quality Nursing on Recovery after Thoracic Surgery - Yujing Zhou; Ming Xu (Emergency Medicine International)
Objective. To observe the feasibility and safety of rapid rehabilitation nursing in the perioperative period of thoracoscopic treatment of lung cancer patients. Rapid rehabilitation nursing was compared with conventional perioperative nursing to explore its clinical efficacy, i.e., its advantages in improving postoperative comfort, postoperative rehabilitation efficiency, and hospitalization cost of patients undergoing thoracoscopic lung cancer resection. Methods. We carried out a retrospective analysis of 337 lung cancer patients who underwent lobectomy in our thoracic surgery department from July 2019 to June 2021, of which 168 lung cancer patients whose perioperative care method was traditional rehabilitation care were classified as A and 169 lung cancer patients who started to implement the intelligent medical intervention method in the department in September were classified as intelligent medical B. By reviewing patient cases and departmental statistics, general information, length of stay, hospitalization cost, complication rate, pain score, bowel movement recovery time, and pulmonary function index of the two groups A and B were compared. Nursing satisfaction was investigated by using a questionnaire. All the data in the study were processed and analyzed using SPSS 17.0 software. Results. There were no differences in preoperative general data, pathological findings, preoperative underlying diseases, lesion involvement sites, and postoperative TNM stages (P>0.05), which were comparable; the incidence of postoperative pulmonary infection and atelectasis complications, postoperative hospitalization time, and hospitalization cost were lower in group B than in group A; the postoperative chest tube drain placement time was shorter in group B than in group A, and the difference between the two groups was statistically significant (P<0.05). The incidence of postoperative pain and discomfort in group B was lower than that in group A, and the difference between the two groups was statistically significant (P<0.05); the incidence of postoperative chest pain, bleeding, pneumothorax, pulmonary infection, and atelectasis in group B was lower than that in group A, and the difference between the two groups was statistically significant (P<0.05). Conclusion. Intelligent medical rehabilitation nursing has good application value in thoracoscopic lung cancer surgery. Applying the concept of intelligent medical rehabilitation nursing provides an important experimental basis and theoretical basis for improving the postoperative survival quality and clinical symptoms of patients undergoing thoracoscopic lung cancer resection, which helps to promote the postoperative recovery of patients with thoracoscopic lung cancer, improves the recovery efficiency of patients and their overall quality of life, and is superior to the conventional nursing group.